2021
DOI: 10.1186/s12886-021-02048-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the optical quality after SMILE and FS-LASIK for high myopia by OQAS and iTrace analyzer: a one-year retrospective study

Abstract: Background To compare the correction effect and optical quality after small-incision lenticule extraction (SMILE) and femtosecond laser assisted laser in situ keratomileusis (FS-LASIK) for high myopia. Methods 51 high myopia eyes after SMILE and 49 high myopia eyes after FS-LASIK were enrolled and divided into two groups retrospectively. The OQAS and iTrace analyzer were used for optical quality inspection. Between the two groups the spherical equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…Nowadays, it is well accepted to use small incision lenticule extraction (SMILE) to correct low-to-moderate myopia [ 1 , 2 ]. For high myopia correction, SMILE also brought satisfying prognosis [ 3 , 4 ], however, SMILE has its inherent limitations such as thick ablation depths, limited ablation zones and increased aberrations, SMILE could increase the risk of dry eye [ 5 ], myopic regression [ 6 ], haze [ 7 ] and corneal ectasia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is well accepted to use small incision lenticule extraction (SMILE) to correct low-to-moderate myopia [ 1 , 2 ]. For high myopia correction, SMILE also brought satisfying prognosis [ 3 , 4 ], however, SMILE has its inherent limitations such as thick ablation depths, limited ablation zones and increased aberrations, SMILE could increase the risk of dry eye [ 5 ], myopic regression [ 6 ], haze [ 7 ] and corneal ectasia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, however, RMS of coma was comparably low in the TCAT group, but the difference wasn’t statistically significant. On the contrary, Yin Y et al found lower coma aberration at 1 month after SMILE than FS-LASIK, which may be due to high myopic correction and iTrace analyzer measurement ( 24 ). Some studies also found lower corneal SA after SMILE compared to FS-LASIK ( 13 15 ).…”
Section: Discussionmentioning
confidence: 96%
“…e results showed that the UCVA values of the three groups before surgery, 2 weeks after surgery, 1 month after surgery and 3 months after surgery were similar (P > 0.05), suggesting that these three surgical treatment methods could effectively improve the incorrected visual acuity of myopic patients and improve the symptoms of distance vision loss. e reasons for this may be as follows: all three procedures, SMILE, FS-LASIK, and SBK, were corneal refractive surgeries based on laser technology, and with laser technical support, these three procedures had the advantages of short treatment time (the required pulse can be obtained in a very short time), small focusing space, high accuracy, and little damage to surrounding tissues and organs [10]. e cornea has the effect of providing most of the refractive power for the eye.…”
Section: Discussionmentioning
confidence: 99%